Managers Shaping the Service Triangle: Navigating Resident and Worker Interests Through Work Design in Nursing Homes. Issue 1 (February 2021) - Vermeerbergen, Lander; McDermott, Aoife M.; Benders, Jos
Managers play a key role in shaping the service triangle and navigating stakeholder interests within this. In health care, labor shortages are prompting consideration of the consequences of care delivery for service users and staff. Here, the authors consider how senior nursing home managers tasked with balancing resident and worker interests manage tensions using work design. The findings identify a five-cluster typology, reflecting variations in how managers from 20 Flemish nursing homes operationalize the same resident-centered care model. Managers purposively shape a different service triangle in each operationalization, variously prioritizing benefits for residents, seeking the golden mean, or attempting to suppress tensions.